2015
DOI: 10.1037/fam0000048
|View full text |Cite
|
Sign up to set email alerts
|

Family functioning in the context of parental bipolar disorder: Associations with offspring age, sex, and psychopathology.

Abstract: Previous research has shown that families with a parent who has bipolar disorder (BD) may experience family functioning difficulties. However, the association between family functioning and psychopathology among offspring of parents with BD, and offspring characteristics that may moderate this association, remains poorly understood. This study examined the cross-sectional associations between family functioning (cohesion, expressiveness, and conflict) and psychopathology in 117 offspring (ages 5-18) of 75 pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 78 publications
1
40
0
Order By: Relevance
“…[44][45][46][47][48] This familial aggregation suggests a potential relevance of both inherited genes, which can be tested by molecular genetic analyses, and the ''inherited'' familial environment, which is also known to be potentially impaired in the face of parental psychopathology. 49,50 In the search for relevant BD-related genes, several genome-wide association studies (GWASs) conducted in the past years have identified multiple loci with a small effect that may account for heritability, [51][52][53][54][55][56][57][58][59][60][61][62] including 30 recently discovered loci encoding ion channels, neurotransmitter transporters, and synaptic components. 63 None of these single nucleotide polymorphisms (SNPs), Figure 1 Etiology of bipolar disorders.…”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…[44][45][46][47][48] This familial aggregation suggests a potential relevance of both inherited genes, which can be tested by molecular genetic analyses, and the ''inherited'' familial environment, which is also known to be potentially impaired in the face of parental psychopathology. 49,50 In the search for relevant BD-related genes, several genome-wide association studies (GWASs) conducted in the past years have identified multiple loci with a small effect that may account for heritability, [51][52][53][54][55][56][57][58][59][60][61][62] including 30 recently discovered loci encoding ion channels, neurotransmitter transporters, and synaptic components. 63 None of these single nucleotide polymorphisms (SNPs), Figure 1 Etiology of bipolar disorders.…”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
“… 44 - 48 This familial aggregation suggests a potential relevance of both inherited genes, which can be tested by molecular genetic analyses, and the “inherited” familial environment, which is also known to be potentially impaired in the face of parental psychopathology. 49 , 50 …”
Section: Genetics and Epigenetics Of Bipolar Disordermentioning
confidence: 99%
“…Adult psychopathology often co‐occurs with other conditions that also constitute risk factors for children's development, such as unemployment, poverty, marital problems, and family instability (Freed et al., ; Gassman‐Pines, Ananat, & Gibson‐Davis, ). Moreover, when both parents have psychopathology, which is common, the risk of poor child outcomes increases (Kahn, Brandt, & Whitaker, ; Wesseldijk et al., ).…”
Section: Psychopathology In Parents and Children Are Inextricably Linkedmentioning
confidence: 99%
“…The third mechanism of risk transmission is through exposure to other types of stressors, such as increased family conflict, which is associated with development of psychopathology in children (Freed et al., ; Goodman & Gotlib, ). The fourth and final mechanism, and the one that is best understood, is parenting quality.…”
Section: Psychopathology In Parents and Children Are Inextricably Linkedmentioning
confidence: 99%
“…In model 3, we additionally adjusted for the other parent's age at childbirth. Because maternal and paternal ages were strongly correlated (Pearson correlation = 0.67), the variance inflation factor (VIF) was used to check the models for co‐linearity (Freed et al, ; Kutner, Nachtsheim, & Neter, ). In all models, the VIFs were approximately 1.9 and 1.8 for paternal and maternal age, respectively.…”
Section: Methodsmentioning
confidence: 99%